THE INFLUENCE OF THE IMMUNOFLOR COMPLEX PROBIOTIC PRODUCT ON THE EGG PRODUCTIVITY OF THE DEKALB WHITE CROSS OF LAYING CHICKEN - Semenov, V.G.; Alekseev, I.A.; Kozak, S.S.; Aubakirov, Kh.A.; Alentayev, A.S.; Basonov, O.A.; Boronin, V.V. (Scientific Journal of Pedagogy and Economics, 2020)
The quality of the received products directly depends on the state of the microflora of the gastroin-testinal tract that is reflected, in particular, on the egg productivity of laying hens. As a result, the use of biologically safe preparations, namely, probiotics, is becoming a priority in the poultry industry. This work aims to establish the feasibility and effectiveness of the use of the complex probiotic products Immunoflor in the diet of laying chickens of the Dekalb White Cross. Based on the comprehensive research, the feasibility of using the complex probiotic product Immunoflor in egg production technology to improve the egg-laying capacity and the quality of the obtained eggs of laying hens of the Dekalb White cross was scientifically substantiated and experimentally proven. Against the background of the use of this drug, it was found that the average daily egg-laying capacity in the 1st and 2nd experimental groups exceeded the control layers: on the 150th day - by 9.66% and 8.48%, on the 180th day - 8.8% and 5.04%, on the 210th day - 8.16% and 6.44%, on the 240th day –11.68% and 3.8%, 270th day – 7.72% and 4.84%, on the 300th day – 8.34% and 5.86%. Besides, the average daily egg mass in the 1 and 2 experimental groups was higher than in the control by 4.04 g and 3.1 g or 7.38% and 5.77%; on the 7th day of storage, the average value exceeded by 4.06 g and 3.1 g or 7.53% and 5.87%; on the 14th day - by 4.32 g and 3.16 g, or 8.18% and 6.12%, respectively. It was found that on the 7th day of storage, the mass loss in the 1st and 2nd experimental groups was 1.50% and 1.56%, which is lower than in the control (1.66%). On the 14th day of storage, the mass loss in the 1st and 2nd experimental groups was 1.95% and 2.36%, which is also lower than in the control (2.63%). With the use of the probiotic preparation, the loss in egg mass decreases. On the 7th day of storage, the mass loss in the 1st and 2nd experimental groups was 1.50% and 1.56%, which is lower than in the control group (1.66%). On the 14th day of storage, the mass loss in the 1st and 2nd experimental groups was 1.95% and 2.36%, which is also lower than in the control (2.63%).